PELATIHAN E-LEARNING SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DI ERA NEW NORMAL BAGI GURU-GURU SD 020 RAMBAH HILIR - Pipit Rahayu; Eripuddin; Wirda Jannatul Jannah; Andri Donal (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
In the field of education, the Covid-19 pandemic has had a significant impact on the learning process. Interaction and face-to-face processes in the classroom cannot take place as they should. Therefore, several government policies in educational institutions to stop the spread of COVID-19 include an appeal for all students and teachers to carry out the learning and teaching process from home. This of course raises new problems where the activities of teachers in preparing interactive learning strategies, techniques and media remotely through online media certainly cannot all be mastered. Moreover, interactive learning media that have so far relied a lot on software or programs on computers and the internet. For teaching staff or teachers in schools, especially in basic education, competence and skills in using interactive learning media are needed as are teachers at SDN 020 Rambah Hilir. In this training, the applications that were socialized were the Google Classroom and Zoom Meeting applications. With this training, the output targets achieved are increasing the knowledge, skills and competencies of SDN 020 Rambah Hilir teachers in using E-Learning as an interactive learning medium to support the teaching and learning process in the current New Normal Era.